Membongkar Privasi: Pengungkapan Gugatan Perceraian di Media Sosial - Roulinta Yesvery Sinaga (LUTUR Law Journal, 2024)
The disclosure of divorce petition reasons on social media is often presented in written form. Divorce issues can become headlines in mass media, characterized by subjective perspectives from informants or sources explaining the reasons for the divorce. The viral divorce issue of Ria Ricis and Teuku Ryan on the Instagram account "lambe turah" became public consumption. The divorce petition reasons, including issues of marital intimacy, family involvement, and poor communication, sparked netizen discussions and negative comments. This study employs a normative juridical method to examine the disclosure of divorce petition reasons on social media through a case approach. It explores the application of legal norms in legal materials that are analyzed in depth. The study results indicate that the divorce petition process in court has strict rules, including the principle of closed sessions to protect the privacy of the parties involved. However, disclosing divorce petition reasons on social media can violate privacy, defame, and negatively impact children's well-being. Although there is no explicit prohibition, such disclosure can be legally accountable. Therefore, it is crucial to maintain confidentiality and adhere to applicable regulations when handling divorce cases.